The Cultural Work : Maroon Performance in Paramaribo, Suriname - Campbell, Corinna, 1981- (Book collections on Project MUSE., 2020)
"How do people in an intensely multicultural city live alongside one another while maintaining clear boundaries? This question is at the core of Corinna Campbell's fascinating study The Cultural Work, which illustrates how the Maroons (descendants of escaped slaves) of Suriname, on the northern coast of South America, have used culture-representational performance to sustain and advocate for their communities within Paramaribo, the capital. Based on the author's long-term fieldwork, The Cultural Work focuses on three distinct collectives: Kifoko, Saisa, and Fiambaknown locally as "cultural groups" (cultureel groepen), all of which specialize in the music and dance traditions of the Maroons of Suriname and neighboring French Guiana. Weaving together performance analysis, ethnography, and critical theory, Campbell demonstrates the broad spectrum of functions and meanings that culture-representational performance can have, while highlighting competing pressures that feature prominently in the lives of Maroons in Paramaribo. She suggests that ambivalence-fundamental to the folkloric enterprise and magnified here by the urban Maroons' social circumstances-enhances possibilities for social criticism for performers and audiences alike. A vital contribution to scholarship that seeks to broaden our knowledge of the cultural map of the African diaspora in South America, Latin America, and the Caribbean, this interdisciplinary book will be a valuable resource for scholars and students of ethnomusicology, dance studies, performance studies, and anthropology."--